Management Risk Appetite as an Determinant of Bank Value and Performance: Theoretical Perspective and Empirical Evidence from Indonesia - Handi Handi; Ronald Rulindo (Eduvest - Journal of Universal Studies, 2025)
This study examines the influence of the Management Risk Appetite Index (MRPI) on the value and financial performance of banks in Indonesia during the 2019–2023 period. The MRPI is constructed based on nine key indicators, covering both company-level dimensions—such as capital adequacy, credit risk, market risk, operational risk, and non-performing loans—and individual-level dimensions, including board size, gender diversity, academic qualifications, and the number of independent commissioners. The findings reveal that a higher MRPI is positively associated with firm value, indicating that banks with greater risk appetite tend to be more attractive in the eyes of the market. However, the effect on financial performance is mixed. While certain aspects of performance benefit from increased risk appetite, others, particularly related to efficiency and profitability, may experience negative impacts. This suggests a higher risk appetite does not automatically translate into stronger financial performance. The study also highlights the significant effects of the COVID-19 pandemic on banking operations, showing that the crisis influenced various performance indicators differently. Additionally, control variables such as bank size and age demonstrate consistent yet varying impacts on both value and performance, depending on the specific metric used. These results underline the importance of aligning risk appetite with governance structures and strategic objectives. For bank owners, regulators, and stakeholders, this implies the need for thoughtful selection of board members and commissioners, considering factors such as education, gender diversity, independence, and experience in risk management to support balanced and sustainable growth.